Potential Uses of Environmental Impact Assessment Report for Environmental Dispute Resolution in Vietnam - Tuan, Can Anh; Co, Hoang Xuan; Lien, Nguyen Thi Hoang (VNU Journal of Science: Natural Sciences and Technology, 2012)
Abstract. Environmental Impact Assessment (EIA) is a mandatory legal procedure for investment projects in Vietnam (the LEP 2005). EIA report is a base for authority agencies to make decision on investment project approvement and a foundation for environmental management agencies to control and inspect the implementation of legal regulations on project environmental protection. Therefore, the results of EIA report are valuable not only in terms of science but also in terms of law in environmental management and environmental dispute solutions relating to projects’ activities. However, in fact, environmental impact assessment in Vietnam still discloses restrictions and does not reflect all its values as a project environmental management tool. This article mentions the legal characters, ability, necessity and some sollutions to use the results of project environmental impact assessment in the industrial production field in Vietnam as one of scientific and legal bases in environmental dispute solution. Keywords: Environmental Impact Assessment (EIA), Environmental Dispute, Law on Environmental Protection (LEP).